2010
DOI: 10.3109/0142159x.2010.497822
|View full text |Cite
|
Sign up to set email alerts
|

Expertise, needs and challenges of medical educators: Results of an international web survey

Abstract: The results of this survey indicate that medical educators face several challenges, with a particular need for more academic recognition, funding and academic qualifications in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
2
39
1
2
Order By: Relevance
“…AEPs expressed a need for better individual and bedside teaching skills, including teaching around cases and providing effective feedback. This differs from a European study of medical educators, 23 which found greater interest in curriculum development and evaluation, learning research methodologies in medical At the same time, our results are also congruent with the recognized need for FD support of academic roles beyond the "clinician-educator." 5,7,13 The trend in these areas is towards the acquisition of skills translatable between all academic domains, primarily communication and people skills.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…AEPs expressed a need for better individual and bedside teaching skills, including teaching around cases and providing effective feedback. This differs from a European study of medical educators, 23 which found greater interest in curriculum development and evaluation, learning research methodologies in medical At the same time, our results are also congruent with the recognized need for FD support of academic roles beyond the "clinician-educator." 5,7,13 The trend in these areas is towards the acquisition of skills translatable between all academic domains, primarily communication and people skills.…”
Section: Discussionsupporting
confidence: 60%
“…Dent et al 26 had a 58% RR, although this was the Australian College's sponsored survey of its members, its survey was far shorter than ours, and financial incentives were provided for completing the study, all of which may account for the higher RR. Huwendiek et al's study 23 of European medical educators had a purview much broader than ours (both in terms of multidisciplinary medical faculty and dozens of countries included), and thus it had a higher overall number of respondents, yet its RR was far lower than ours (4.8%).…”
Section: Limitationscontrasting
confidence: 57%
See 3 more Smart Citations